2013
DOI: 10.1680/si.12.00014
|View full text |Cite
|
Sign up to set email alerts
|

Silica-based superhydrophobic coating by a single-step process

Abstract: Silica-based superhydrophobic coatings were produced on glass substrate by dip-coating process. Colloidal solutions containing nanoparticles of silica synthesized via seed growth method (single-and dual-sized particles) and dispersed in three different solvents, ethanol, silica sol and acidic silica sol, were used. Coatings with dual-sized particles in ethanol showed superhydrophobicity with a water contact angle of 155°. The coating adhesion was improved with the use of acidic silica sol as solvent. Coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…68,[119][120][121][122][123][124][125][126][127][128][129] Review of all the literature and possible applications targeted by the authors exceeds the scope of this review. Only a few examples of commercial products that authors are either aware of or found through the Internet are provided.…”
Section: Applications Of Superhydrophobic Oleophobic Superhydrophilmentioning
confidence: 99%
“…68,[119][120][121][122][123][124][125][126][127][128][129] Review of all the literature and possible applications targeted by the authors exceeds the scope of this review. Only a few examples of commercial products that authors are either aware of or found through the Internet are provided.…”
Section: Applications Of Superhydrophobic Oleophobic Superhydrophilmentioning
confidence: 99%
“…Fluorocarbon polymer coatings are of particular interest for superhydrophobic surfaces due to the extremely low surface energy of fluorine-containing (CF 2 and CF 3 ) functional groups [ 42 ]. Compounds of this type include polymers based on silanes and methacrylates with alkyl and perfluoroalkyl substituents [ 43 , 44 , 45 , 46 ]. Their use is mainly limited by poor adhesion to the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the first approach depends on producing geometrically controlled rough surfaces and reducing the surface energy by adding low surface energy materials, and the second approach solely involves tailoring the low surface energy material by creating roughness at micro-and nanoscales. 2 Proper design of surface topographical feature is required to support aforementioned criteria for superhydrophobicity. In this case, the water droplet rests on the top asperities of the dual scale surface structure and results in Cassie-Baxter regime in which air is supposed to be trapped in rough structure underneath the water droplet and in turn gives a higher WCA.…”
Section: Introductionmentioning
confidence: 99%